2013
DOI: 10.1007/s00436-012-3250-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of microRNAs in male and female adults of Ascaris suum

Abstract: Ascaris nematodes, which cause ascariasis in humans and pigs, are among the most important nematodes from both health and economic perspectives. microRNA (miRNA) is now recognized as key regulator of gene expression at posttranscription level. The public availability of the genome and transcripts of Ascaris suum provides powerful resources for the research of miRNA profiles of the parasite. Therefore, we investigated and compared the miRNA profiles of male and female adult A. suum using Solexa deep sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This is in agreement with the overall female-bias observed for protein-coding genes in both S. mansoni [10] and S. japonicum [11], although a recent expression analysis in S. japonicum showed no gender bias [13]. Recently, a work in the parasitic nematode Ascaris suum showed that microRNAs are differentially expressed between males and females [32]. Although the differences were small and the targeting properties of male and female microRNAs similar, they reported a tendency of male microRNA to target extracellular proteins [32].…”
Section: Discussionsupporting
confidence: 84%
“…This is in agreement with the overall female-bias observed for protein-coding genes in both S. mansoni [10] and S. japonicum [11], although a recent expression analysis in S. japonicum showed no gender bias [13]. Recently, a work in the parasitic nematode Ascaris suum showed that microRNAs are differentially expressed between males and females [32]. Although the differences were small and the targeting properties of male and female microRNAs similar, they reported a tendency of male microRNA to target extracellular proteins [32].…”
Section: Discussionsupporting
confidence: 84%
“…42 Metallothionein genes or pseudogenes were 4 of the 9 mRNAs showing the highest expression in women in PRAX1 (supplemental Table 7A), perhaps due to estrogeninduced increase in cadmium levels that transcriptionally upregulate metallothionein genes. 43 Although miRNAs have been reported to be DE by gender in the Ascaris nematode, 44 we are unaware of prior reports of human miRNA profile comparisons of gender differences in any tissue. In PRAX1, we observed 2 of the 9 miRNAs DE by gender were more highly expressed in women.…”
Section: Effect Of Gender On Rna Expressionmentioning
confidence: 91%
“…Their germline is siRNA pathway dependent, whereas embryogenesis and larval development is dependent on miR pathway. The miR expression profile of male and female worm shared two novel miRs Asu-miR-share-391 and Asu-miR-share-404, the expression of miR-391 was more abundant in male than in female (Xu et al, 2013b). But their role in immune regulation needs to be further investigated.…”
Section: Mir In Nematodementioning
confidence: 99%
“…The comparative miR expression profile of these two species had revealed 13 species-specific miRs that matched with miR4006b of Ciona intestinalis and miR 1957 matched with Mus musculus . Other miRs that could map to metabolic regulation and catalytic and binding function were common to both species (Xu et al, 2013b). Fromm et al (2015) used deep-sequencing method and identified 54 miRNA (42conserved and 13 novel) and isolated miR from extracellular vesicles (EV) also.…”
Section: Mir In Trematodementioning
confidence: 99%